Stereoselective one-pot synthesis of polypropionates - Guo-Ming Ho (Nature Portfolio, 2017)
Polypropionates are present in many natural products possessing high bioactivity and therapeutic value. Here the authors show a strategy for the stereoselective assembly of polypropionates with three or four stereocentres through a process that includes a Diels–Alder reaction, silylenol ether hydrolysis and Baeyer–Villiger oxidation.